Measuring cash flow flexibility of companies: The cumulative index-difference - B. W. Steyn; W. D. Hamman; E. V.D.M. Smit (South African Journal of Business Management, 2002)
Cash is king. Even a highly profitable company can find itself in search of financing due to a lack of cash to honour its obligations. If this situation is only temporary and external sources of finance are freely available, this cash flow obstacle does not have to be detrimental to the stakeholders of the company.However, if the poor cash position of a company is not temporary, but rather an integral part of its structure and a result of its strategy, stakeholder interest may be at risk. Although insolvency is seldom the outcome, such companies find themselves struggling because of their cash flow inflexibility.The cumulative index-difference aims to identify companies that are cash flow inflexible, in order to enable stakeholders to take timely measures to prevent a negative outcome. With adjustments in strategy and preventative measures taken, the cash flow positions can be improved to prevent a disaster.
Keywords: 650